Proximity to inlet channel drives spatial variation in sediment carbon across a lagoonal seagrass meadow - Rachel Schaefer; Phil Colarusso; Juliet C. Simpson; Alyssa Novak; Heidi Nepf (Science of The Total Environment, 2024)

Spatial heterogeneity in sediment and carbon accretion rates within a seagrass meadow correlated with the hydrodynamic intensity - Jiarui Lei; Rachel Schaefer; Phil Colarusso; Alyssa Novak; Juliet C. Simpson; Pere Masqué; Heidi Nepf (Science of The Total Environment, 2023)

Wave damping by seagrass meadows in combined wave‐current conditions - Rachel Beth Schaefer; Heidi Nepf (Limnology and Oceanography, 2022)
Laboratory experiments using an artificial seagrass meadow modeled after Zostera marina measured the impact of following currents on meadow‐induced wave decay as a function of the imposed current velocity , wave velocity , and wave Cauchy number , which is the ratio of hydrodynamic drag force to restoring force due to blade stiffness. For small wave‐induced reconfiguration of individual seagrass blades and the addition of current enhanced reconfiguration, which decreased wave decay relative to pure wave conditions. In contrast, when the wave‐induced reconfiguration was large , the addition of following current did not significantly enhance blade reconfiguration or impact wave damping. Due to canopy drag, the current velocity within the submerged meadow, , was significantly smaller than the depth‐averaged current , and a better prediction of wave decay was achieved using as the relevant velocity. The measured wave decay validated predictions based on a modified Cauchy number, defined for combined waves and current and using the in‐canopy velocity . Practical assumptions to facilitate the prediction of wave decay in the field are discussed and validated.

Flow Structure in an Artificial Seagrass Meadow in Combined Wave-Current Conditions - Rachel B. Schaefer; Heidi M. Nepf (Frontiers in Marine Science, 2022)
Experiments were conducted in a laboratory flume using an artificial seagrass meadow, modeled after Zostera marina , to examine the impact of waves on the vertical structure of time-averaged current, Reynolds stress, and turbulent kinetic energy (TKE) under combined wave-current conditions. With the addition of smaller waves, defined by a ratio of wave velocity to current velocity U w /U c < 2.5, the time-averaged velocity peaked above the meadow, which was similar to pure current conditions. When U w /U c > 2.5, the presence of waves caused the time-averaged velocity to peak near the top of the meadow. For U w /U c > 1 the presence of waves reduced the magnitude of peak Reynolds stress. For all conditions considered, the wake production of turbulence dominated the shear production of turbulence in the meadow. However, the wave velocity was less efficient than the current velocity in generating TKE in the meadow because the movement of the blades forced by the oscillatory fluid motion reduced the relative velocity between the blades and the wave. A modified hybrid model for wake production of TKE in a flexible canopy under combined wave-current conditions was proposed to account for the relative contributions of waves and currents. Wake production of TKE was dominated by waves when U w /U c > 1 and dominated by currents when U w /U c < 1. The models and observations proposed in this study contribute to an enhanced understanding of the relative influences of waves and currents on seagrass meadow flow structure in realistic combined wave-current conditions.